ELECTRICAL-THERMAL COUPLING OF INDUCTION MACHINE FOR IMPROVED THERMAL PERFORMANCE (Nigerian Journal of Technology, 2016)
This paper summarizes the electrical-thermal coupling of induction machine for improved thermal performance. The interaction of its electrical and mechanical parts leads to an increase in temperature which if not properly monitored may lead to breakdown of the machine. The paper therefore, set out to study the effect of electrical and thermal model on the machine. A two-mass system is used to model the mechanical part of the machine. A lumped parameter method was used in the thermal model of the machine. The system of non-linear ordinary differential equations which describe the thermal behaviour of the machine in transient state were solved numerically using the fourth-order Runge-Kutta method. MATLAB m-files were developed and were used to solve the coupled machine model under transient condition. The thermal resistances and capacitances were determined and calculated with the help of purely dimensional information from the machine geometry and constant thermal coefficients and their values were accepted as inputs by the MATLAB m-files. The results show that the temperature rise for various parts of the machine with the rotor iron and bar having a peak temperature rise of 229oC at approximately 0.15s during motor start-up. http://dx.doi.org/10.4314/njt.v35i4.28